EFEK KOMPOSISI MEDIA HIDROGANIK DAN DOSIS VERMIKOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA KERITING (Lactuca sativa L.) - siti masita adam; Sunawan Sunawan; Nurhidayati Nurhidayati (AGRONISMA, 2020)
This study aims to determine the composition of the planting media that provides the highest growth and yield. Determine the vermicompost dose that gives the best growth and results. Knowing the interaction of the planting media composition and vermicompost dose which gives the highest growth and yield. The study was conducted on February 27 - June 15, 2019 in the Compost Laboratory of the Faculty of Agriculture, Malang Islamic University and a plastic house on Jalan MT. Haryono 198A, Dinoyo Village, Malang City. The results of this study also showed a real interaction at the age of 7 days where M1V5 treatment (cocopeat 55% + zeolite 15% + 30% sand, with a dose of 250 g / pot, gave the highest plant height. At the age of 22 hst separately treatment M1 ( cocopeat 55% zeolite 15% sand 30%) gave a better plant height than M2 treatment (cocopeat 55% zeolite 30% sand 15%) while the highest dose treatment was at V4 but not significantly different from V2, V3, V5 and treatments with inorganic fertilizer, the treatment of vermicompost dosage shows that the dosage of V3 (150 g / pot), V4 (200 g / pot), V5 (250 g / pot)) gives an average value of high total fresh weight of plants. Whereas high total economic fresh weight was found at V2-V5 dose (100-250 g / pot) and significantly different at V1 (50 g / pot), and was not significantly different from inorganic fertilizer.